Heat Stress Impacts on Lactating Cows Grazing Australian Summer Pastures on an Automatic Robotic Dairy - Osei-Amponsah, R.; Dunshea, F.R.; Dunshea, B.J.; Cheng, L.; Cullen, B.; Joy, A.; Abhijith, A.; Zhang, M.H.; Chauhan, S.S. (animals, 2020)
The objective of this study was to measure the impacts of summer heat events on physiological parameters (body temperature, respiratory rate and panting scores), grazing behaviour and production parameters of lactating Holstein Friesian cows managed on an Automated Robotic Dairy during Australian summer. The severity of heat stress was measured using Temperature-Humidity Index (THI) and impacts of di erent THIs—low ( 72), moderate (73–82) and high ( 83)—on physiological responses and production performance were measured. There was a highly significant (p 0.01) e ect of THI on respiratory rate (66.7, 84.7 and 109.1/min), panting scores (1.4, 1.9 and 2.3) and average body temperature of cows (38.4, 39.4 and 41.5 C), which increased as THI increased from low to moderate to high over the summer. Average milk production parameters were also significantly (p 0.01) a ected by THI, such that daily milk production dropped by 14% from low to high THI, milk temperature and fat% increased by 3%, whilst protein% increased by 2%. The lactation stage of cow had no significant e ect on physiological parameters but a ected (p 0.05) average daily milk yield and milk solids. Highly significant (p 0.01) positive correlations were obtained between THI and milk temperature, fat% and protein% whilst the reverse was observed between THI and milk yield, feed intake and rumination time. Under moderate and high THI, most cows sought shade, spent more time around watering points and showed signs of distress (excessive salivation and open mouth panting). In view of the expected future increase in the frequency and severity of heat events, additional strategies including selection and breeding for thermotolerance and dietary interventions to improve resilience of cows need to be pursued.
Research Article
Keywords: milk production; panting scores; respiration rate; thermal camera